Gestión financiera en el sector de salud veterinaria - Suárez Suárez, Jéssica Yolanda (2021)
The research work on Financial Management in the Veterinary Health Sector was carried out because currently companies in the veterinary health sector in the province of Santa Elena lack efficient financial management, ignorance of their weaknesses results in an economic imbalance and financial, deficiencies in its planning and control of resources. The objective of the research was to analyze financial management by diagnosing the current situation of the sector, the analysis of financial statements, proposing a model that allows improving the profitability of companies in the veterinary health sector that are in this situation of business vulnerability. For the development of the work the mixed approach was used, the type of research used was descriptive, in relation to the temporal scope it was longitudinal because a company was studied during several economic periods. The population was ten companies in the sector, the sample was one company. The techniques for data collection were the interview, the observation guide and the documentary analysis of financial statements.....